Effect of COVID-19 on the embedded industrial seminar implementation based on TVET undergraduate students perception - Yaacob, Mohd Rusdy; Mohd Saad, Wira Hidayat; Maslan, Mohd Nazmin; Abal Abas, Zuraida; Wan Daud, Wan Mohd Bukhari (2023)
COVID-19 has massively hit the whole world in many different aspects of life including the delivery of embedded industrial seminar (EIS), which is one of the significantly important academic activities in Technical and Vocational Education and Training (TVET) higher institutions. EIS, which was previously conducted on a face-to-face (F2F) basis has been urged to undergo a transition to the online alternative. It is therefore a great interest in conducting a preliminary study to evaluate the effect of COVID-19 on this transition, based on the undergraduate students’ perception. The survey was conducted on 129 respondents who have participated in an online EIS organized by the Faculty of Electrical Engineering, Universiti Teknikal Malaysia Melaka (UTeM), through a set of questionairres on an online form. Besides revealing a high degree of agreement on the direct impact of COVID-19 on the EIS implementation, the results also possess significant potential for the online EIS to equally replace the F2F implementation in the future.